2022
DOI: 10.1021/acs.molpharmaceut.2c00407
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Cell-Derived Exosomes for Cancer Therapy

Abstract: Exosomes are a type of extracellular vesicles secreted by cells in normal or pathological conditions for cell–cell communication. With immunomodulatory characteristics and potential therapeutic properties, immune-cell-derived exosomes play an important role in cancer therapy. They express various antigens on their surface, which can be employed for antigen presentation, immunological activation, and metabolic regulation, leading to the killing of cancerous cells. In addition, immune-cell-derived exosomes have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 161 publications
0
7
0
Order By: Relevance
“…reported that B lymphocytes secrete antigen-presenting vesicles ( 36 ). Since then, more and more studies have found that exosomes secreted by immune cells interact with cells in the immune system to regulate immune responses ( 37 ). Therefore, these membranous vesicles are being explored as potential immunotherapeutic reagents.…”
Section: Immune Cell-derived Exosomes and Diabetesmentioning
confidence: 99%
“…reported that B lymphocytes secrete antigen-presenting vesicles ( 36 ). Since then, more and more studies have found that exosomes secreted by immune cells interact with cells in the immune system to regulate immune responses ( 37 ). Therefore, these membranous vesicles are being explored as potential immunotherapeutic reagents.…”
Section: Immune Cell-derived Exosomes and Diabetesmentioning
confidence: 99%
“…Exosomes derived from immune cells have immunomodulatory and therapeutic properties, and are crucial for the treatment of cancer. Immune cell-derived exosomes have attracted a lot of interest as a drug delivery platform for effective anticancer therapy, due to their outstanding biocompatibility, low immunogenicity, and high loading capacity [ 40 ]. Some researchers have found that the nanovesicles cultured with primary immune cells contain immunoglobulin, which can be used for immunotherapy [ 41 ].…”
Section: Exosomes and Drug Delivery Systemsmentioning
confidence: 99%
“…Depending on the origin of the exosome, different responses can be initiated in the target cell. For example, exosomes derived from immune system cells can lead to the expansion or suppression of tumor growth based on their origin ( 34 , 35 ). Due to their immunomodulatory properties, the presence of MSC-derived exosomes can lead to tumor progression ( 36 ).…”
Section: Tumor-derived Exosomes In Pancreatic Cancer Progressionmentioning
confidence: 99%